Prevalencia de Eperythrozoon spp. en cerdos y patogenicidad en portadores esplenectomizados - Cruz, E.=700 1 Delgado, L.; Gonzalez, R.
(Es, En)
Ilus., 8 ref.
Keywords: EPERYTHROZOON; BACTERIA; MORBOSIDAD; CERDO; CUBA; EPRITROZOONOSIS